Health-seeking behavior and its determinants for non-communicable diseases in India - a systematic review and meta-analysis - Madhumitha Haridoss; Dhruva Nandi; Raji Rajesh Lenin; Shiny P. John; V. V. Anantharaman; Rajiv Janardhanan (Frontiers in Public Health)
IntroductionIndia faces a growing burden of non-communicable diseases (NCDs), particularly diabetes, cardiovascular conditions, and cancer, straining the healthcare system. Given the urgent need for prevention and management, a systematic review and meta-analysis (SRMA) of health-seeking behaviors for NCDs is essential to guide targeted interventions to improve health outcomes.MethodsThe SRMA protocol was registered in PROSPERO (CRD42023476381) and conducted adhering to the Preferred Reporting Items of Systematic reviews and Meta-Analysis (PRISMA) 2020 guidelines. PubMed-Medline and Scopus databases were searched from inception to October 27, 2023. Eligible studies focused on adults (>18 years) with NCDs covered under the National Programme for prevention and Control of Cancer, Diabetes, Cardiovascular Diseases and stroke (NPCDCS). Data extraction and risk of bias assessment were conducted using predefined criteria. Meta-analysis of quantitative data was performed using DerSimonian and Laird random-effect model.ResultsFrom 2,917 identified studies, 64 were included in the SRMA, with 40 suitable for meta-analysis. The meta-analysis revealed that 72.72% (95% CI 59.48–85.97%, I2 = 99.97%) of individuals sought treatment for existing health conditions, with 73.09% (95% CI 54.01–92.16%, I2 = 99.18%) preferring allopathy, compared to 8.89% (95% CI 5.56–12.22%, I2 = 86.73%) preferring Alternative medicine with a significant heterogeneity. Major barriers to seeking treatment included illness not considered serious [0.4785 (95% CI 0.4556–0.5013)] and financial constraints [0.3263 (95% CI 0.1457–0.5069)], with delays in cancer treatment attributed to lack of disease awareness [0.5091 (95% CI 0.0294–0.9888)] and painlessness [0.4502 (95% CI 0.3312–0.5692)]. Private healthcare facilities (51.26, 95% CI 42.85–59.67%) were preferred over government facilities (33.78, 95% CI 28.10–39.45%).ConclusionThis SRMA provide a comprehensive overview of health-seeking behavior for NCDs in India. The findings underscore the complex interplay of socioeconomic, cultural, and systemic factors influencing healthcare access and outcomes. Targeted interventions addressing barriers identified in this review are imperative for improving public health and reducing the burden of NCDs in India.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023476381.